A TDMA Based Scheme for the Construction of R2R Communication Platform - Liaw, Der-Cherng; Yeh, Chia-Wei; Lo, Sung-Ming (My University, 2014)
In the previous study (Liaw and Kuo, 2012), a preliminary version of the Time Division Multiple Access (TDMA)-based communication platform had been successfully tested to provide the function of wireless hopping data transmission. However, that design was only valid for the consecutive nodes which are close-by. A modified design was proposed in (Liaw, Wang and Lai, 2013) by using self-design Wireless Sensor Network (WSN) nodes to investigate the feasibility of the application in short range data communication. The effect of the packet size and distance between two consecutive nodes on the performance of remote data transmission was also studied. Instead, in this paper, we propose another scheme for time division wireless monitoring transmission protocol (TDWMTP). This design is based on IEEE 802.11a standard with the transmission method of TDMA (Time Division Multiple Access) to enhance and implement the function proposed in (Liaw, Wang and Lai, 2013). Experimental results demonstrate the success of the proposed design.
Keywords: DTMA; R2R; ITS